Microwave Assisted Synthesis and Antimicrobial Screening of Pyrazoline-5-ones - SHIRADKAR, MAHENDRA; KALE, RAJESH; BAVISKAR, BHUSHAN; DIGHE, RAJENDRA (Asian Journal of Chemistry, 2010)
4-Amino-2,3-dimethyl-1-phenyl-3-pyrazoline-5-one (1) was condensed with different aromatic aldehydes to yield Schiff bases (2a-i). The Schiff bases on cyclization with chloroacetyl chloride in presence of triethyl amine as catalyst furnished azetidine-2-ones (3a-i). The Schiff bases (2a-i) on cyclization with mercaptoacetic acid in the presence of anhydrous aluminium chloride as catalyst offered thiazolidine-4-ones (4a-i). The compounds were synthesized in good yield and characterized by their TLC, chemical analysis and spectral data and were subjected to antimicrobial activity.